HIV in Geriatrics - Ainun, Nur; Yunihastuti, Evy; Roosheroe, Arya Govinda (UI Scholars Hub, 2016)
Through both prolonged survival and late acquisition of the disease, numbers of older adults with HIV are climbing. Along with ageing process is an accumulation of HIV-associated non-AIDS related comorbidities, creating a complex patient group affected by multi-morbidity along with polypharmacy, functional decline and social issues.